(untitled) (International Journal of Agricultural Extension and Education, 2025)
This study examined the Impact of Agricultural TechnologyAdoption on Farming Practices: A Field Survey of Farmers in Pambegua, Kubau LGA, Kaduna State. A field survey design was employed, targeting 40 purposively selected smallholder farmers actively engaged in crop production. Data were collected using structured questionnaires and interviews, and analyzed through descriptive statistics, supported by chi-square tests to establish associations. Findings revealed that male farmers (70%) dominated agricultural activities, with the majority being within the productive age range of 31–50 years. Education played a key role, as farmers with secondary education (35%) demonstrated greater awareness of agricultural technologies. Exposure to technologies was mainly through mobile phones (37.5%) and radio/TV programs (25%), while advanced digital platforms remained underutilized. Adoption levels were highest for improved seeds (35%) and fertilizers/pesticides (30%), but relatively low for mechanization (20%) and irrigation (15%). Major constraints identified included high costs of inputs and devices (35%), poor infrastructure such as network and electricity (25%), lack of training (20%), and limited access to credit (20%). Farmers suggested training and capacity building (30%), provision of subsidies (25%), improved extension services (25%), and affordable loans (20%) as strategies to enhance adoption. The study concludes that while smallholder farmers in Pambegua are receptive to input-based technologies, structural and financial barriers hinder wider adoption. Strengthened extension services, policy-driven subsidies, and targeted training are recommended to bridge the gap between technology availability and farmer utilization.